The rich north-west, the poor middle-east: Consumption in EU households - Marlena Piekut (Comparative Economic Research. Central and Eastern Europe, 2015)
The aim of paper is to analyze household consumption in EU countries in the 21st century. The two hypotheses posited have been confirmed. The start of the 21st century saw an increase in consumer spending in EU households and reduction in the disparities between households of different countries. At the end of the first decade there was a stabilization in consumer spending. The differences in consumption between households can be considered as a) the effect of freedom of choice, and b) a consequence of specific restrictions that do not allow for an appropriate level of funds to meet household needs. Households with the most favourable situation are located in the United Kingdom and Austria. The most unfavourable situation can be observed in the households of Estonia, Latvia, Poland, Romania and Bulgaria.
Keywords: 330; households; EU; consumer expenditures; disproportions